MORTALITY RATES AND YIELD PER RECRUIT IN NEMIPTERUS JAPONICUS (BLOCK) - Krishnamurthy, B (Indian Journal of Fisheries, 2011)
Both the yield per recruit in Weight ( Y ^ / R ) and in numbers (Yj^/R) inNemipterus japonicus (Bloch) increase with increased fishing mortality i.e., withincreased fishing mortality, yield increases to an asymptote. Since the rate ofexploitation works to about 3% only, it seems reasonable to remark that thestocks of N. japonicus are very much underexploited